Pilomatricoma: An unusual cause of lump in a male breast. Issue 3 (29th May 2017) - Kapoor, Anu; Narayanan, Ramakrishna; Tandon, Ashwani; Santosh, Arun Kumar
ABSTRACT: We present the case of a 48‐year‐old man who presented with a painless, progressively increasing lump in the left breast. The mammographic and sonographic appearance of the lesion was suspicious for malignancy. Fine needle aspiration cytology and histopathologic examination confirmed the diagnosis of pilomatricoma. © 2017 Wiley Periodicals, Inc. J Clin Ultrasound 46 :209–211, 2018